(untitled) (Research, Society and Development, 2021)
Polypharmacy is the term used to refer to the use of multiple drug combinations and has received much attention due to its numerous health impacts and the frequency with which it is used. Thus, polypharmacy is a critical problem that can affect anyone, being more harmful to the elderly due to the potential risks of adverse and collateral events, which can influence oral and systemic health. The objective of this protocol is to present methodological steps for conducting a scoping review in order to explore the impacts of polypharmacy on the oral health of the elderly, mapping and summarizing the evidence on the most recurrent manifestations and pathological conditions due to the condition studied, in addition to verifying how studies have been conducted and identifying gaps in the literature. This protocol was developed according to the recommendations of the Joanna Briggs Institute Manual and registered in the Open Science Framework. PubMed via MEDLINE, Science Direct (Elsevier), Web of Science, Scopus, LILACS, and Google Scholar will be used to search the studies. The data will be extracted and presented in the form of tables and/or images and in descriptive form, as indicated in the checklist proposed by PRISMA-ScR. It is expected that this protocol will enable the realization of a scoping review, with consistent methodology and, from it, the attainment of greater knowledge about the impacts of polypharmacy on the oral health of the elderly, broadening the vision that we have on the subject.